KNOWLEDGE, ATTITUDE AND PRACTICES AMONG WOMEN BETWEEN 15-49 YEARS TOWARDS UTILISATION OF FAMILY PLANNING SERVICES AT ITOJO HOSPITAL, NTUNGAMO DISTRICT. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Turyasingura , Denis (Student’s Journal of Health Research Africa, 2023)
Background: Family planning refers to a conscious effort by a couple to limit or space the number of children they have through the use of contraceptive methods. Study Objective: The broad objective was to determine the factors affecting the utilization of family planning services among women of reproductive age 15-49 years at Itojo Hospital. Study Method: This was a descriptive cross-sectional study conducted in the Ntungamo district at Itojo Hospital. Simple random sampling was used to recruit 81 respondents aged 15-49 years and data was analyzed using Excel. Results: The study revealed that all the respondents 100% were knowledgeable about family planning meth- ods, the most important source of information was health personnel 63.0%, 53.1% reported that their husbands had a bad attitude and the mostly used family planning method was implanted at 38.2%. Conclusion: Most of the respondents were highly knowledgeable about family planning methods. The majority of them had a bad attitude towards family planning as they cited that it causes infertility and contradicts religion. All the respondents had used family planning and the mostly used family planning method was implants. Recommendation: There is a need for the government to extend the family planning services up to the village level to increase accessibility by the community, for example through awareness campaigns with help from Community Owned Resource People and VHTs. Future researchers to look at the factors influencing the choice of family planning methods among women of reproductive age to increase utilization. The health facility carries out outreach services on family planning services to areas that are far away from the facility to reduce the long distances most respondents have to travel to the health facility.